IMPLEMENTASI RESTORATIVE JUSTICE DALAM PENEGAKAN HUKUM PAJAK - Sarwirini - (Universitas Airlangga, 2014)
In order to prevent the tax evasion, the tax law can be enforced by tax collection, tax assessment and tax investigation. This paper is based on legal research using statute and conceptual approaches. The legal issues of this paper focus on two problems; the philosophical basis and general philosophy of restorative justice in the law enforcement and whether the philosophical and restorative justice principles become a foundation for the tax law enforcement in Indonesia. The result of the paper indicates that the philosophical and the restorative justice principle has become the foundation for regulation and tax enforcement rather than repressive or retributive justice. Persuasive approach focused on tax payers and officers’ consensus is the best mechanism for tax evasion, not only related on civil and criminal matters, but also for administrative. The implementation of restorative justice principle will be appropriate if the principle is accompanied by good governance principles.Keywords: tax, restorative justice, law enforcement, persuasive, and concensus.